Comparison of Panfish Catch and Retention by Four Modified Fyke‐Net Designs. (9th October 2019) - Krogman, Rebecca M.
Abstract: Modified fyke nets are commonly used across the USA for sampling littoral fish communities, including crappie Pomoxis spp., Bluegill Lepomis macrochirus, Redear Sunfish L. microlophus, and other panfish, and are recommended for standard sampling in all lentic waters. Traditional modified fyke nets in Iowa differed from the American Fisheries Society standard in two primary ways: throat configuration and number of funnel‐shaped throats. Given the historical data sets derived from traditional modified fyke nets and the reticence to convert to a net design with lesser catch rates, a formal evaluation of net designs was needed. Four combinations of throat configuration (square or restricted) and number of throats (one or two) were included in this study. To examine retention, all four net designs were stocked with fish and checked for retained fish the following day, enabling calculation of probability of retention and relative risk of escape. To examine catch efficiency and precision, nets were deployed in 13 southern Iowa lakes and reservoirs. Catch rates were compared using generalized linear mixed models predicting catch with net design. Net design was a significant factor affecting both retention and catch efficiency, with the traditional Iowa net consistently capturing and retaining as many or more fish than other net designs. The number of net sets needed to capture 125 fish of each species and to achieve a target precision level was also calculated for each net design; two‐funneled designs minimized the necessary number of net sets for Bluegills, crappies, and Redear Sunfish. Considerations for standard modified fyke‐net refinement include the addition of a second funnel and restriction of the cod end throat.